Investigations of aluminum fluoride as a new cathode material for lithium-ion batteries - Owen, N.; Zhang, Qi (Springer, 2017)
Four differently prepared aluminum fluoride samples were tested as cathode materials for rechargeable lithium batteries. The charge–discharge results showed an initial capacity of over 900 mAh g−1 for most of the samples at a voltage of around 2 V, giving specific energy densities of over 7405 kJ kg−1, higher than many commercial materials. The cycling results showed an initial high-capacity with rapid capacity fade. The reversible conversion reaction of aluminum fluoride was shown to follow the reduction of AlF3 into LiF and Al during discharge and upon charge Al would be oxidized to form AlF3 and Li again. It was found that not all the AlF3 would be oxidized due to the large surface/interfacial energy produced by the production of nano LiF and Al particles and the large reduction in size from the initial particles to the reduced phase. There was formation of unwanted Li3AlF6 due to the reaction of AlF3, LiF, and LiPF6 which also reduced the cycling capacity.
Keywords: AlF3; Cathode; Li-ion batteries; Electrochemical properties